PERBANDINGAN REGULASI KESEHATAN ANTAR NEGARA: DAMPAKNYA TERHADAP KUALITAS PELAYANAN KESEHATAN - Heriani Heriani; Loso Judijanto; Amina Ramadana N (CV. Adiba Aisha Amira, 2025)
This study examines the comparison of health regulations between countries and their impact on the quality of health services. The study found that countries with strict health regulations tend to have higher standards of health services, which are reflected in improved patient safety and competence of medical personnel. In contrast, countries with lax regulations often face challenges in maintaining quality of care, including a higher risk of malpractice and patient dissatisfaction. Thus, harmonisation of health regulations at the global or national level is recommended to reduce inequalities in healthcare quality and improve overall public health. This study underscores the importance of consistent and adaptive regulation to improve health outcomes across countries.